The Constant and the Troubled in the Egyptian Policy towards the Internal Palestinian Files between 2006 and 2014_ National Reconciliation as a Model_ - guenfoude, Saadia; benadi, Mohamed tahar (The Algerian Historical Journal, 2026)
This study seeks to highlight the Egyptian foreign policy position on the Palestinian national reconciliation file in the period from 2006 to 2014, which was characterized by the succession of three political leaders to rule Egypt, by tracing the paths of Egyptian foreign policy towards the Palestinian cause in general and the national reconciliation file in particular, and revealing the declared motives and The secret of the successive Egyptian leaders in their dealings with the Palestinian national reconciliation file, especially after the political situation worsened starting in 2006, and about the means used in that, as well as examining the seriousness of each of them in trying to end the division and resolve the Palestinian-Palestinian conflict. In its various stages, the Egyptians had different directions and goals, and different means in their failed attempts to end the Palestinian political and geographical division.